Relationship between RS time and the severity of chronic obstructive pulmonary disease - Çağlar Özmen; İbrahim Yıldız; Hüsamettin Sazlıdere; Mehmet Sait Gürevin; Yavuz Karabağ; İbrahim Rencüzoğulları; Pınar Özmen Yıldız; Cengiz Burak (Cukurova Medical Journal, 2021)
Purpose: The aim of our study was to determine whether the RS time measured on an electrocardiogram is associated with the severity of chronic obstructive pulmonary disease (COPD). Materials and Methods: The study population was made up of 100 COPD patients with a mean age of 63 ± 10 years (86% were males). These patients were divided into the mild and moderate COPD (GOLD 1–2) group (n = 45) and the severe and very severe COPD (GOLD 3–4) group (n = 55) according to the Global Initiative for Chronic Obstructive Lung Disease (GOLD) stages. These groups were compared with each other. Results: Heart rate, P wave axis, QRS axis, RS time, and incidence of right bundle branch block were significantly higher in patients with severe and very severe COPD. In the multivariable analysis, heart rate, P wave axis, and RS time (odds ratio = 1.081) were the independent predictors of severe and very severe COPD. The receiver operating characteristic curve analysis showed that the best RS time cutoff value for the prediction of severe and very severe COPD was 60 ms, with a sensitivity of 69.1% and a specificity of 66.7%. Conclusion: RS time simply measured on an electrocardiogram may be a useful screening test for the quick estimation of patients with severe and very severe COPD.